Effect of Electroacupuncture at Auricular Vagus Nerve on Depression and Anxiety-Like Behaviours of Mice with Preweaning Maternal Separation - WU Nan; WANG Qiang; LI Yongfeng; WU Yuwei; QIAO Haifa; LI Guohui; YUAN Wei (康复学报)
ObjectiveTo observe the effect of electroacupuncture at auricular vagus nerve on depression and anxiety-like behaviours of mice with preweaning maternal separation (PMS), and to explore its possible neural mechanism.MethodsA total of three male and nine female adult C57BL/6 mice were paired randomly by one male and three females for breeding. After pregnancy, the female mice were divided randomly into control group and maternal separation group according to the random number table method. After birth, the offspring of the maternal separation group were divided randomly into model group and electroacupuncture (EA) group according to the random number table method, with 10 mice in each group. After anesthesia, EA intervention was performed at the bilateral concha auricular area of the EA group with continuous wave, frequency at 2 Hz, intensity at 1 mA, once a day, 10 minutes a time, six days a course, lasting for two courses. The control group and model group were anesthetized as same as the EA group, but without EA intervention. After intervention, open field test, elevated plus maze test and tail suspension test were conducted to detect the depression and anxiety-like behaviours; immunofluorescence method was used to detect the expression level of c-fos in the prefrontal cortex (PFC) and dorsal raphe nucleus (DRN) and the number of 5-HT neurons in the DRN.Results(1) Behavioral indicators: compared with the control group, total distance traveled in the open field, the percentage of time spent in the center zone, the time spent in the open arm, the distance traveled in the elevated plus maze, the entries into the open arm of the model group decreased significantly, the freezing time increased significantly, and the differences were statistically significant (P<0.05). Compared with the model group, the percentage of time spent in the center zone, total distance traveled in the open field, the time spent in the open arm, the distance traveled in the elevated plus maze, the entries into the open arm of the EA group increased significantly, the freezing time of the EA group decreased significantly, and the differences were statistically significant (P<0.05). (2) C-fos expression level and the number of 5-HT neurons: compared with the control group, the number of c-fos neurons in the DRN and PFC brain regions of the model group decreased significantly, and the number of 5-HT neurons in the DRN brain region of the model group decreased significantly (P<0.05). Compared with the model group, the number of c-fos neurons in the DRN and PFC brain regions of the EA group was significantly higher, and the number of 5-HT neurons in the DRN brain region of the EA group was significantly higher (P<0.05).ConclusionElectroacupuncture at auricular vagus nerve can improve depression and anxiety-like behaviours of PMS mice, and the specific mechanism may be related to the regulation of c-fos expression in DRN and PFC brain regions and the number of 5-HT neurons in DRN brain regions.